The high-mobility-group transcription factor Sox8 is a negative regulator of osteoblast differentiation. - Sock, Elisabeth; Wegner, Michael; et al. (The Journal of Cell Biology, 2005)
Bone remodeling is an important physiologic process that is required to maintain a constant bone mass. This is achieved through a balanced activity of bone-resorbing osteoclasts and bone-forming osteoblasts. In this study, we identify the high mobility group transcription factor Sox8 as a physiologic regulator of bone formation. Sox8-deficient mice display a low bone mass phenotype that is caused by a precocious osteoblast differentiation. Accordingly, primary osteoblasts derived from these mice show an accelerated mineralization ex vivo and a premature expression of osteoblast differentiation markers. To confirm the function of Sox8 as a negative regulator of osteoblast differentiation we generated transgenic mice that express Sox8 under the control of an osteoblast-specific Col1a1 promoter fragment. These mice display a severely impaired bone formation that can be explained by a strongly reduced expression of runt-related transcription factor 2, a gene encoding a transcription factor required for osteoblast differentiation. Together, these data demonstrate a novel function of Sox8, whose tightly controlled expression is critical for bone formation.
UnivIS-Import:2015-03-09:Pub.2005.med.IB.LPCIPDBI.thehig